Influence of the peritoneal lavage with bupivacaine on the survival and resistance of colonic anastomoses performed under fecal peritonitis in rats - Camargo,Michel Gardere (2013)
PURPOSE: To evaluate the effects of peritoneal lavage with bupivacaine on survival and initial resistance of anastomosis on distal colon, performed under peritonitis or not. METHODS: Forty rats, weighing from 300 to 350g (321.29±11.31g), were randomly divided in four groups and underwent laparotomy and anastomosis on the distal colon six hours after induction of peritonitis by intraperitoneal injection of autologous fecal material or not. Group 1: No peritonitis and lavage with 3ml NS; Group 2: No peritonitis and lavage with 8 mg.kg-1 (± 0.5 mL) of 0.5% bupivacaine added to 2.5 mL of NS; Group 3: Peritonitis and lavage with 3ml NS; Group 4: Peritonitis and lavage with 8 mg.kg-1 (± 0.5 mL) of 0.5% bupivacaine added to 2.5 mL of NS. Necropsies were performed on the animals that died and the time of death was recorded. Surviving animals were submitted to euthanasia on the fifth post-operative day and Total Energy of Rupture biomechanical test (TER) was applied. RESULTS: Group 4 showed survival increase compared to Group 3, without statistical significance. Group 3 presented the smallest average TER, with statistical significance. CONCLUSION: Peritonitis increased mortality and influenced negatively the resistance of colic anastomosis in rats. Peritoneal lavage with bupivacaine increased anastomotic resistance.